Pengaruh Gaya Kepemimpinan Transformasional dan Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan Studi pada PT. Sari Bumi Mulia Kecamatan Singosari Kabupaten Malang - Asrori, Mukhamad Sobih; Djaelani, Abdul Kodir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study examines the impact of transformational leadership style and quality of work life on the performance of employees at PT. Sari Bumi Mulia, Singosari, Malang. The research involved 43 company representatives. The data analysis method employed was quantitative analysis using multiple linear regression. Hypothesis testing included testing concurrent hypotheses (F-test) and partial hypotheses (t-test). The results indicated that both independent variables significantly influenced the dependent variable simultaneously. According to the partial test results, transformational leadership style and quality of work life significantly affect the employee performance at PT. Sari Bumi Mulia, Singosari, Malang. Keywords: Transformational Leadership Style, Quality Of Work Life, Employee Performance